PROBLEMATIKA PENDIDIKAN ISLAM DI ERA GLOBALISASI SERTA SOLUSI PEMECAHANNYA - Muhammad Indra Eka Putra; Nurmaini; Nafsi Latifah; Hendrizal (STKIP Subang, 2024)
This paper discusses the problems of Islamic education in the era of globalization and solutions to solve them. This research method uses library research or literature study In collecting data, the author uses a literature study which is research by collecting data from various sources such as books, journals, the internet, and other relevant sources regarding the problems of Islamic education in the era of globalization. The results of this study are: 1) Understanding the problem, 2) The meaning of Islamic Education, 3) The basics of Islamic Education, 4) The purpose of Islamic education, 5) The problems of Islamic Education in the era of Globalization, 6) Solutions to the problems of Islamic Education in the era of Globalization. The conclusion of this paper in achieving the success of Islamic education in facing the challenges of globalization requires the development of a curriculum that combines Islamic values and global learning. In addition, the use of technology in learning methods that are in line with religious principles also needs to be involved. Thus, Islamic education can face and respond to global developments with a comprehensive approach and integration between Islamic values and the development of the global world.